Women as Victims of Online Gender-Based Violence in a Victimology Perspective - Aqila Shafiqa Aryaputri; Handar Subhandi Bakhtiar (PALAR | PAKUAN LAW REVIEW, 2026)
The development of digital technology has given rise to Online Gender-Based Violence (KBGO), especially in the form of the dissemination of non-consensual pornography that has a multi-layered impact on victims. This study aims to analyze the form of victimization experienced by victims and evaluate legal protection in the case of Rebecca Klopper based on Decision Number 616/Pid.Sus/2023/PN JKT. SEL using a feminist victimology perspective. This research is a normative legal research with legislative, conceptual, and case approaches. The results of the study show that victims not only experience primary victimization through the recording and dissemination of intimate content without consent, but also revitalization that is strengthened by social responses in the form of victim blaming, stigmatization, and objectification that reflect patriarchal constructions in interpreting the victim's position. Normatively, victim protection has been regulated in the Sexual Violence Crime Law, the Electronic Information and Transaction Law, and the Witness and Victim Protection Law. However, the implementation has not been fully from the perspective of the victim, as can be seen from the focus of the verdict which is limited to the perpetrators of the dissemination without revealing the perpetrators of the initial recording and the principle of restorative justice has not been accommodated. A comparison with the setting in Singapore shows the importance of a legal approach that is not only repressive, but also oriented towards the comprehensive recovery of victims in responding to the character of digital-based violence. Keywords: Online Gender-Based Violence (KBGO), Feminist Victimology, Restorative Justice.